Use of Windfall Gold Sale Profits-Further Considerations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
In April 2011, Executive Directors held a preliminary discussion on the use of the profits of SDR 6.85 billion from the Fund's limited gold sale. They noted their expectation that at least SDR 4.4 billion of the profits would be placed in an endowment within the Investment Account, and affirmed their support for the 2009 financing package for low-income countries (LICs), including the distribution to the Fund's membership of up to SDR 0.7 billion from the profits linked to gold sales, with the expectation that most members will return equivalent funds to the Poverty Reduction and Growth Trust (PRGT). There was a wide range of views among Directors on the three main options presented for the windfall of SDR 1.75 billion, but no consensus favoring a single option. The main options presented included use of resources linked to the windfall to boost the capacity of the PRGT, counting the windfall towards precautionary balances, or investing the windfall profits as part of the Investment Account's endowment. Many Directors indicated that they could support a combination of two or more of the main options.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet